A Boron Alkylidene–Alkene Cycloaddition Reaction: Application to the Synthesis of Aphanamal. (9th August 2017) - Liu, Xun; Deaton, T. Maxwell; Haeffner, Fredrik; Morken, James P.
Abstract: We describe an unusual net [2+2] cycloaddition reaction between boron alkylidenes and unactivated alkenes. This reaction provides a new method for the construction of carbocyclic ring systems bearing versatile organoboronic esters. Aside from surveying the scope of this reaction, we provide details about the mechanistic underpinnings of this process, and examine its application to the synthesis of the natural product aphanamal.